Patent of Invention Award (5 family members) - Angastiniotis, Nicos (My University, 2026)
UNITED STATES PATENT, Patent Number US5776264, "Method for producing amorphous based metals", July 7, 1998, patent owners: N.V. UNION MINIERE S.A., THE UNITED STATES OF AMERICA AS REPRESENTED BY THE SECRETARY OF THE NAVY; also registered as: CANADIAN PATENT, Patent Number CA2190422, SOUTH AFRICAN PATENT, Patent Number ZA9609689, EUROPEAN PATENT, Patent Number EP0800883, JAPANESE PATENT, Publication Number JP09-309704; SOUTH KOREAN PATENT, Publication Number KR970069200 (A); cited by patents assigned to companies such as Honda Motor Co., Honda R&D (USA), Central Research Institute of Electric Power Industry (Japan), China Petroleum Corp., Osram Sylvania (USA), NanoDynamics (USA), Concept Alloys (USA), American Scientific Materials Technologies(USA), Conexant Systems (USA), Inframat Corporation (USA)
Keywords: Arts and entertainment